Transfusion-associated malaria [Transfüzyonla bulaşan sitma] - (:unkn) unknown (My University, 2002)
Malaria is the world's most important parasitic infection. Despite intensive eradication programmes, the prevalence of malaria in tropical and subtropical countries is extremely high. Malaria can be transmitted by transfusion of any blood component likely to contain even small number of red cells. In non-malarious countries, mainly because of delay in diagnosis, post-transfusion malaria has a relatively high fatality rate; it can be particularly serious in pregnant women and in splenectomized or immunosuppressed patients.